Вплив плацентарних клітин мезенхімального походження на слизову оболонку шлунка щурів - Луженецька, Валентина; Кузнєцова, Галина; Світіна, Ганна; Гарманчук, Людмила; Шаблій, Володимир; Рибальченко, Володимир; Luzhenetska, Valentyna; Kuznietsova, Halyna; Svitina, Anna; Harmanchuk, Ludmyla; Shablii, Volodumyr; Rybalchenko, Volodumyr (Східноєвропейський національний університет імені Лесі Українки, 2015)
Досліджено вплив плацентарних мезенхімальних клітин алогенного та ксеногенного походження на сли- зову оболонку фундального відділу шлунка щурів. Показано, що мезенхімальні стовбурові клітини щурів і людини мають негативний вплив на слизову оболонку шлунка, що прямо пропорційний кількості уведення клітин. It is established that transplantation of placenta derived cells (PC) of mesenchymal origin to healthy rats causes inflammatory changes in the gastric mucosa manifested by edema, vascular congestion, lymphocytic and eosinophilic infiltration. No structural and functional changes of gastric mucosa caused by introduction of fewer PCs amount (0.5*106 cells per rat) were observed, whereas maximal investigated rat RC amount causes increase of secretion of the parietal cells and inhibition of the secretion of the main cells. Human PC when transplanted in amount of 2*106 cells per rat promotes occurrence the attributes of parietal and main cells enhanced secretion.
Influence of Placenta Derived Cells of Mesenchymal Origin on Rat Gastric Mucosa.
Keywords: клітинна терапія; мезенхімальні стовбурові клітини; стовбурові клітини щурів; стовбурові клітини людини; слизова оболонка шлунка; cell therapy; mezenhymal stem cells; rat stem cells; human stem cells; gastric mucosa